Utility of 128-row multidetector CT in quantitative evaluation of global left ventricular function in patients with coronary artery disease - Mohamed I. Amin; Hanan A. Hassan; Mohamed I.A. Mousa (The Egyptian Journal of Radiology and Nuclear Medicine, 2018)
Purpose: Is to compare the role of 128 MDCT in quantitative evaluation of left ventricle function in patients with coronary artery disease compared to 2D echocardiography. Patients and methods: Fifty patients with suspected coronary artery disease underwent contrast enhanced MDCT using retrospective gating without dose modulation. Ten phases of cardiac cycle were processed to assess end-systolic and end-diastolic phase at LV short-axis view. 2DSE was performed in the same day. LVSV, LVDV, LFEF, LVSV were calculated using the Simpson's method in MDCT and modified Simpson's method in echocardiography. Results: LVSV, LVDV, LVSV, LFEF were 74.30 ± 24.92, 185.46 ± 56.25, 84.15 ± 33.16, 48.88 ± 13.32 respectively on MSCT and 71.43 ± 21.93, 182.31 ± 56.49, 81.74 ± 32.88, 47.82 ± 13.64 respectively on echocardiography with excellent correlation between the modalities (P < 0.001) using linear regression analysis. A Bland-Altman analysis showed that MDCT had slightly higher LVSV, LVDV, and LVSV, LFEF values with mean value of differences of 2.9, 3, 2.4 and 1% respectively. Conclusion: MDCT is an accurate method for quantitative evaluation of global left ventricular function compared to 2D echocardiography. Keywords: MDCT, Global left ventricular function, Coronary artery disease